Providing the basis for a patient-centred and effective screening for cancer-related fatigue (MERLIN study): design of a longitudinal observational study - Blickle, Patricia; Haussmann, Alexander; Holzner, Bernhard; Berger, Anne Katrin; Steindorf, Karen; Schmidt, Martina (BMJ open, 2023)
Introduction  Cancer-related fatigue (CRF) is a frequent and burdensome sequela of cancer and cancer therapies. It can persist from months to years and has a substantial impact on patients’ quality of life and functioning. CRF is often still not adequately diagnosed and insufficiently treated. According to guideline recommendations, patients should be routinely screened for CRF from cancer diagnosis onwards. We will investigate how an effective screening should be designed regarding timing, frequency, screening type and cut-o ff points. Methods and analysis  MERLIN is a longitudinal observational study that will include 300 patients with cancer at the beginning of cancer therapy. The main study centre is the National Center for Tumour Diseases Heidelberg, Germany. Patients answer five items to shortly screen for CRF at high frequency during their therapy and at lower frequency during the post-treatment phase for 18 months. Further, CRF is assessed at wider intervals based on the Cella criteria, the Brief Fatigue Inventory impact scale, the quality of life fatigue questionnaire (QLQ-F A12) and the fatigue and cognitive items of the quality of life core questionnaire (QLQ-C 30), both of the European Organisation for Research and Treatment of Cancer. Important psychological, socio-d emographical or medical factors, which may exacerbate CRF are assessed. All assessments are performed online. Receiver operating curves, areas under the curve, sensitivity, specificity, positive and negative predictive values and likelihood ratios will be calculated to determine optimal short screening modalities. Ethics and dissemination  The study was approved by the ethics committee of the Medical Faculty of the Heidelberg University, Germany (approval number: S-3 36/2022). Written informed consent is obtained from all participants. The study is conducted in full conformance with the principles of the Declaration of Helsinki. Results will be published in peer-reviewed scientific journals, presented at conferences and communicated to clinical stakeholders to foster the implementation of an effective CRF management. Trial registration number  ClinicalTrials.gov; registration number: NCT05448573.
Gesehen am 04.12.2023